DEVELOPMENT OF ENVIRONMENTAL AND HEALTH-CONSCIOUS BEHAVIOUR IN LOWER PRIMARY ENGLISH LESSONS - Csenger, Gyöngyi (Tudásmenedzsment, 2024)
Health as a value was already respected in the life of the oldest communities, and they tried to create harmony in their lives. The perception of health, the positive attitudes to wards health are established in childhood. Families and the educational work carried out in public education institutions, occupy a special place in this process. Health education and promotion, as important elements of education for sustainability, prepare students to respect health as a value and be able to contribute to the creation of a sustainable soci ety and economy in an active and constructive way. The purpose of this study is to present the theoretical background and pedagogical practice of health education by examining the Moson-Sopron county, and a survey performed with the headteachers and English teachers of the elementary schools of this county. We assume that these schools have a Health education program, health education is included in the curriculum of all subjects, project work is considered a significant method. Environment and health education can be supported by project work, highlighting sustainability and the importance of environment protection. The novelty of the pilot environmental education project - presented in this paper - is the module focusing on environmental hazards, as this is an extracurricular topic. The pre- and post-survey carried out among the 4th grade learners of a volunteer primary school before and after the project implementation proved that they had some basic knowledge about some areas of sustainability and healthy life but the project could help them to widen and deepen their knowledge and to understand the link between environment and their health.